2009
DOI: 10.1530/eje-09-0414
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of low O6-methylguanine DNA methyltransferase expression in invasive macroadenomas of Cushing's disease

Abstract: Context: Crooke's cell adenoma (CCA), characterized by massive Crooke's hyaline change in corticotroph adenoma, causes a rare subtype of Cushing's disease. In contrast to ordinary corticotroph adenomas, CCAs are generally aggressive and present as invasive macroadenomas, which are refractory to both surgery and radiotherapy and have a high-recurrence rate. Moreover, some patients with CCA present with distant or craniospinal metastases. Currently, there are no effective standard therapies for CCA. Objective: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 23 publications
4
62
0
1
Order By: Relevance
“…These included tumor necrosis and hemorrhage, 15,23 tumor degenerative and cystic changes, 22 and tumor shrinkage. 2,10,11,14,[19][20][21]24 These changes could be observed as early as 2 months after the onset of temozolomide treatment.…”
Section: Morphologic Changesmentioning
confidence: 98%
See 1 more Smart Citation
“…These included tumor necrosis and hemorrhage, 15,23 tumor degenerative and cystic changes, 22 and tumor shrinkage. 2,10,11,14,[19][20][21]24 These changes could be observed as early as 2 months after the onset of temozolomide treatment.…”
Section: Morphologic Changesmentioning
confidence: 98%
“…To date, 6 patients with pituitary carcinomas have received treatment with temozolomide 10,[12][13][14]17,19,[23][24][25] (Table 1). These included 4 men and 2 women ages 26 to 77 years (mean, 49.8 years).…”
Section: Pituitary Carcinomasmentioning
confidence: 99%
“…In all cases, surgery was performed by the same surgeon (SY) who has experience with more than 2500 pituitary surgeries. Samples were examined by routine histological methods and immunohistochemical staining as previously described (21,22). They were classified as CCA when the percentage of Crooke's hyaline change in tumor cells was O50%, with the remaining tumor samples being considered as nonCrooke's cell adenoma (non-CCA) (1,21).…”
Section: Patientsmentioning
confidence: 99%
“…Samples were examined by routine histological methods and immunohistochemical staining as previously described (21,22). They were classified as CCA when the percentage of Crooke's hyaline change in tumor cells was O50%, with the remaining tumor samples being considered as nonCrooke's cell adenoma (non-CCA) (1,21). Sixteen tumor samples were identified as CCA from 209 samples (7.7%), and 15 out of 16 samples were available for RNA extraction.…”
Section: Patientsmentioning
confidence: 99%
“…These alterations could influence functional pathways dictating tumor phenotype, including invasive behavior. A potential relationship between MGMT status and tumor invasion was described in invasive Crooke's cell adenomas, which have decreased expression of MGMT compared with noninvasive ordinary-type adenomas of Cushing's disease (12), and in gastric carcinoma, in which MGMT promoter methylation was associated with lymph node invasion (13). In the context of GBM, Brandes and colleagues (14) recently observed that following treatment, GBM tumors with MGMT promoter methylation recurred at more distal sites from the initial radiation field.…”
Section: Introductionmentioning
confidence: 99%